2018
DOI: 10.1371/journal.pcbi.1005945
|View full text |Cite
|
Sign up to set email alerts
|

Identifying human diamine sensors for death related putrescine and cadaverine molecules

Abstract: Pungent chemical compounds originating from decaying tissue are strong drivers of animal behavior. Two of the best-characterized death smell components are putrescine (PUT) and cadaverine (CAD), foul-smelling molecules produced by decarboxylation of amino acids during decomposition. These volatile polyamines act as ‘necromones’, triggering avoidance or attractive responses, which are fundamental for the survival of a wide range of species. The few studies that have attempted to identify the cognate receptors f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 66 publications
2
29
0
1
Order By: Relevance
“…Exactly the same position, 6.58, appears to fulfil a similar function in several neurotransmitter and hormone receptors 30 , beta adrenergic receptors 13 and the gonadotropin releasing hormone receptor 27 , 33 . In a recent modelling study on two human TAARs, 6.58 was hypothesized to serve as floodgate to remove the solvent shell from the ligand, before it reaches the internal binding site 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Exactly the same position, 6.58, appears to fulfil a similar function in several neurotransmitter and hormone receptors 30 , beta adrenergic receptors 13 and the gonadotropin releasing hormone receptor 27 , 33 . In a recent modelling study on two human TAARs, 6.58 was hypothesized to serve as floodgate to remove the solvent shell from the ligand, before it reaches the internal binding site 34 .…”
Section: Discussionmentioning
confidence: 99%
“…77 Notably, a recent study reported an association between the VN1R1 polymorphisms and sexual behavior (in particular, number of one-night stands) in women, but not in men. 82 At this point, it is unclear whether TAAR-induced signaling affects psychosexual functions in humans. 74 Interestingly, the TAAR5 ligand trimethylamine occurs at high levels in adult male mouse urine and is equally attractive to both sexes.…”
Section: Main Olfactory Epitheliummentioning
confidence: 99%
“…79 Human TAAR5 is also activated by trimethylamine, 80 but as well by a substance in rotting (but not fresh) fish 81 ; a purely computational approach predicts that the molecules putrescin and cadavarine are ligands for human TAAR6 and TAAR8, respectively. 82 At this point, it is unclear whether TAAR-induced signaling affects psychosexual functions in humans.…”
Section: Main Olfactory Epitheliummentioning
confidence: 99%
“…Isopentylamine is a reported endogenous agonist for TAAR3 (11), while agmatine is only currently described as an agonist for TAAR 13c that has currently only been found to be expressed in zebra fish [24]. The diamine binding site through which agmatine interacts with TAAR13c is, however, conserved in both human and rodent TAAR6 and TAAR8 isoforms [24,25] making them potential sites through which agmatine effects might be mediated. The N,N-dimethylalkylamines, meanwhile, are agonists at TAAR7 and TAAR9 isoforms [16].…”
Section: Discussionmentioning
confidence: 99%